Hyperlipidemia and apolipoprotein E are associated with intraocular pressure of thyroid-associated ophthalmopathy in a Chinese population: a cross-sectional study - Chen, Yu; Qi, Xin; Wang, Jingya; Xu, Huayang; Sun, Yushi; Wang, Ling; Zhou, Xingchen; He, Mingqian; Zhao, Jiarui; Zhang, Jinbo; He, Hairong; Guo, Hui; et al. (Frontiers in Endocrinology, 2024)
Objective This study aimed to explore the clinical characteristics of thyroid-associated ophthalmopathy (TAO) with hyperlipidemia and to identify the key lipid indicator. Methods Patients with TAO were recruited to this study and divided into two groups based on the presence of hyperlipidemia. TAO patients with hyperlipidemia were further classified based on the type of hyperlipidemia. Basic and clinical information of the patients were collected, and comparisons between groups were carried out. Correlation analyses, regression analyses, and stratified analysis were performed to assess the correlations and relationship of the serum lipids with the ophthalmic indicators. Results A total of 273 patients with TAO were recruited, including 158 patients with hyperlipidemia and 115 patients without hyperlipidemia. Patients with hyperlipidemia, especially those with mixed hyperlipidemia, exhibited high intraocular pressure (IOP). Spearman’s correlation analysis and partial correlation analysis showed that apolipoprotein E (ApoE) was positively related to IOP levels after controlling for confounding factors, including age, gender, BMI, smoking history, triiodothyronine (T3), and thyrotropin (thyroid-stimulating hormone, TSH). Moreover, multiple linear regression obtained a regression equation including ApoE, gender, age, and BMI and showed that elevated ApoE levels were associated with elevated IOP [β = 0.072, 95% confidence interval (CI) = 0.037–0.155, p = 0.030]. Stratified analysis highlighted the impact of ApoE on IOP in younger patients (≤48 years), female patients, patients with normal BMI (<24 kg/m2), and patients with a shorter course of ophthalmopathy (≤6 months). Conclusion Overall, higher IOP levels were observed in patients with hyperlipidemia, especially those with mixed hyperlipidemia. Notably, a higher ApoE was identified as an independent risk factor for higher IOP. This finding confirmed the close relationship between TAO and lipid metabolism and provides a new insight into the pathogenesis research and the long-term management of TAO.